Salmonella Pathogenicity Island 1 (SPI-1) and Its Complex Regulatory Network - Lou, Lixin; Zhang, Peng; Piao, Rongli; Wang, Yang (Frontiers in Cellular and Infection Microbiology, 2019)
Salmonella species can infect a diverse range of birds, reptiles and mammals, including humans. The type III protein secretion system (T3SS) encoded by Salmonella pathogenicity island 1 (SPI-1) delivers effector proteins required for intestinal invasion and the production of enteritis. The T3SS is regarded as the most important virulence factor of Salmonella. SPI-1 encodes transcription factors that regulate the expression of some virulence factors of Salmonella, while other transcription factors encoded outside SPI-1 participate in the expression of SPI-1-encoded genes. SPI-1 genes are responsible for the invasion of host cells, regulation of the host immune response, e.g., the host inflammatory response, immune cell recruitment, and apoptosis, and biofilm formation. The regulatory network of SPI-1 is very complex and crucial. Here, we review the function, effectors and regulation of SPI-1 genes and their contribution to the pathogenicity of Salmonella.